CHANGING EMPHASES IN SEXUALITY EDUCATION AMONG ADOLESCENCE - BABATUNDE, OBALASE STEPHEN; BOLANLE, OGBEYE GBEMISOLA; AKINTUNDE, SMART ADESEGHA (IJRDO- Journal of Educational Research, 2016)
The current study was designed to investigate the changing emphasis on sexualityeducation in Nigeria. This brings about consciousness and awareness in the subject matters.Despite various awareness programmes of sexuality education in the mass and electronicmedia young people engage in risky sexual behaviour for several reasons .Such reasons includethe following: Economic factor, Cultural factors, Lack of adequate information, Poverty andSocial consequences. The need to inform young people about the causes and consequences ofuncontrolled rapid population growth has become paramount hence the National PopulationPolicy of 1988 which was recently revised and officially launched in February 2005, was put inplace with emphases on population education as a potential vehicle to translate the populationPolicy into action (Forrest & Silverman , 1989).Sexuality education is a process of learningabout how an individual can be comfortable with all aspects of being human. Sexualityeducation can also be described as a process of providing information, skills and services thatenables person to adopt safe sexual behaviours including abstainess, non-penetrative sex such ashugging, holding hands, as well as correct and consistent use of condom. Sexually healthybehaviours also include seeking care from trained health workers during incidence of anyreproductive morbidity such as sexually transmitted infection (STIs), unwanted pregnancy andinfertility (Adesokan, 2009).Sexuality Education has changed from traditional concept tomodern concept .Increased Knowledge about sexuality matters. Attitudinal and BehaviouralChange, Abstinence as the key for effective sexuality education, Emphasis on sexuality educationbring about prevention of unwanted pregnancy, Increase Gender Equality and Prevention ofGender Violence. Emphasis on sexuality education bring about assertiveness skills, life andfamily building skills..The provision of sexual and reproductive health services for young peopleand the development of life-skills and sex education inside and outside of schools which centeron the realities of young people’s lives and their needs , as expressed by adolescents themselvesremain in an early stage.